Coordination Models and Languages 12th International Conference, COORDINATION 2010, Amsterdam, The Netherlands, June 7-9, 2010. Proceedings - Clarke, Dave.; Agha, Gul.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 12th International Conference on Coordination Models and Languages, COORDINATION 2010, held in Amsterdam, The Netherlands, in June 2010, as one of the federated conferences on Distributed Computing Techniques, DisCoTec 2010. The 12 revised full papers presented were carefully reviewed and selected from 28 submissions. The papers cover a wide range of topics including the application of coordination in wireless systems; multicore scheduling; sensor networks; event processing; data flow networks; and railway interlocking.
Observables for Mobile and Wireless Broadcasting Systems -- Behavioural Contracts with Request-Response Operations -- NOW: A Workflow Language for Orchestration in Nomadic Networks -- A Calculus for Boxes and Traits in a Java-Like Setting -- JErlang: Erlang with Joins -- A Hybrid Visual Dataflow Language for Coordination in Mobile Ad Hoc Networks -- Compositional Construction of Real-Time Dataflow Networks -- Coordinating Resource Usage through Adaptive Service Provisioning in Wireless Sensor Networks -- Simulation and Analysis of Distributed Systems in Klaim -- Modelling Railway Interlocking Tables Using Coloured Petri Nets -- Efficient Session Type Guided Distributed Interaction -- Scalable Efficient Composite Event Detection.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Computer Science; Software Engineering; Programming Techniques; Software Engineering/Programming and Operating Systems; Computer Communication Networks; Models and Principles; Information Systems Applications (incl.Internet).